DAMPAK PERLAKUAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 ATAS PAJAK PENGHASILAN PADA UMKM DI GRESIK - Ilmia, Faiqotul; Andriani, Sri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
In achieving the desired development by Indonesia, the government requires revenue from the State Tax Revenue and Non-Tax Revenues. One of the efforts undertaken by the Directorate General of Taxation (DGT) is enacted Government Regulation No. 46 of 2013, the tax base used is the gross turnover of each month at 1 % final income tax rates. The emergence of these regulations is to provide convenience for taxpayers in determining the amount of income tax payable, but enactment of these rules in the middle of giving trouble for taxpayers in the calculation, depositing and reporting taxes for the year 2013. Purpose of this study was to determine the impact of treatment of PP 46 of 2013 on income tax on Micro, Small and Medium Enterprises (SMEs) in Gresik skull cap industry. This study used a qualitative descriptive approach with the aim of obtaining a picture of the object that is easily observed in the form of words on the focus of research on the impact of the enactment of Regulation 46 of 2013. The 3 (three) object of research is no skull cap Industry SMEs in Gresik . Data analysis aims to simplify the data processed, making it easy to read and interpret. Data were collected by means of observation, interviews, documentation. Analysis of the data through three stages: data reduction, data display, and conclusion. The results showed that the enactment of Regulation 46 of 2013 not only creates difficulties in terms of computation, depositing and reporting just as effective mid-year, but still there who do not know the regulations in terms of both has been the enactment of these regulations and in terms of the calculation mechanism. As for other effects of the government’s enactment of legislation, namely the amount of income tax payable is higher than the income tax calculations using norm bookkeeping or net income.